Lebenssituation von jungen Frauen mit Ullrich-Turner-Syndrom nach dem Ende der Wachstumshormontherapie: Ergebnisse einer Umfrage in Deutschland - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Brämswig, Jürgen; Hauffa, Berthold P.; Holterhus, Paul Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Günter K.; Wabitsch, Martin; Wölfle, Joachim (Deutsche Medizinische Wochenschrift, 2019)
Introduction Psychosocial problems such as anxious personality, low self-esteem, late separation from home and/or late sexual experience have been described in girls and women with Turner syndrome (TS). Methods The study was performed in 2015 based on a questionnaire that was sent out to 779 women with TS aged 25 years (median). The questionnaire was devised by a French team and used with their permission. In all, 130 questionnaires (16.7%) could be evaluated. The questions from the individual topics were not always completely answered. Results (mean ± SD). 116 women (89.9%) were not married; 52 women (40%) lived in their parents' home. 47.6% had a high-school/technical diploma or university degree. 60 women (46%) had a job; 51 women (39%) had not completed vocational training. Puberty was induced at the age of 14.2± 2.1 years in 78% of the women. 80% of the women received hormone replacement therapy at the time of the questionnaire survey. 66 of 93 women (71%) found that the disease had a negative influence on emotional life. Love life and sexual relationship was the topic mentioned most frequently by 44 women (66.6%). 116 women answered questions on sexuality. Here, 77% had the first French kiss at the age of 16.4± 3.6 years and 62.4% had sexual intercourse for the first time at the age of 19.0±3.4 years. 81% of the women stated that they had a partner relationship for more than 6 months (94 women had a male partner and 5 had a female partner). The question as to the wish to have children was answered in the affirmative by 89 of 124 women (71.8%); 38.2% desired spontaneous pregnancy and 44.9% had considered in vitro fertilization or adoption. Discussion The women's answers show that care needs to be improved. There are deficits in the topics of family, emotional life, relationships, sexuality, fertility and pregnancy. Therefore, the medical team should also include psychologists and social workers.
CRIS-Team Scopus Importer:2019-07-26
Keywords: emotional life; fertility; questionnaire; sexuality